Comparison of subjective and objective methods of determination of stroke phases to analyse arm coordination in front-crawl - Seifert, L.; Schnitzler, C.; Aujouannet, Y.; Carter, M.; Rourard, A.; Chollet, D. (Biomechanics and Medicine in Swimming X, 2006)
The aim of this study is to evaluate the reliability of the subjective method of determination of the arm stroke phases in front crawl 1) by studying the influence of the expertise level of the operator, and 2) by comparing the phases results deter-mined subjectively by an operator with data obtained from a digitizing process. These two methods were used to calculate an index of coordination (IdC) based on phases durations. The IdC values assessed by the novice operators were higher than those of the expert operators, due to a higher of the pull phase and to a smaller catch phase. Smaller Standard deviations of IdC were observed for experts compared to novices indicating a greater reproducibility in the phases determination. No significant differences of stroke phases and IdC were observed between the results obtained from the expert operators and the digitising process.